2023
DOI: 10.1155/2023/2728719
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning and Medical Image Processing Techniques for Diabetic Retinopathy: A Survey of Applications, Challenges, and Future Trends

Abstract: Diabetic retinopathy (DR) is a common eye retinal disease that is widely spread all over the world. It leads to the complete loss of vision based on the level of severity. It damages both retinal blood vessels and the eye’s microscopic interior layers. To avoid such issues, early detection of DR is essential in association with routine screening methods to discover mild causes in manual initiation. But these diagnostic procedures are extremely difficult and expensive. The unique contributions of the study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Their accuracy in identifying this disease has been outstanding, often outperforming human specialists. This study uses AlexNet and Resnet101 feature extraction techniques to automatically recognize and categorize DR fundus pictures based on severity, allowing patients with high blood sugar-related DR to avoid complications and potentially lose their eyesight ( Fayyaz et al, 2023 ; Uppamma & Bhattacharya, 2023 ). Early diagnosis through automatic detection utilizing modern technology can help prevent consequences like eyesight loss.…”
Section: Deep Learning In Diabetic Retinopathymentioning
confidence: 99%
“…Their accuracy in identifying this disease has been outstanding, often outperforming human specialists. This study uses AlexNet and Resnet101 feature extraction techniques to automatically recognize and categorize DR fundus pictures based on severity, allowing patients with high blood sugar-related DR to avoid complications and potentially lose their eyesight ( Fayyaz et al, 2023 ; Uppamma & Bhattacharya, 2023 ). Early diagnosis through automatic detection utilizing modern technology can help prevent consequences like eyesight loss.…”
Section: Deep Learning In Diabetic Retinopathymentioning
confidence: 99%
“…Several research papers have investigated the prediction of DR utilizing CNN and pre-trained models, including DenseNet, VGG, ResNet, and Inception [19]. Moreover, specific study is required to enhance the efficiency of the deep learning framework [20]. With 94.4% accuracy, Usman et al [4] observed that a pre-trained CNN model detected lesions better.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several research papers have investigated the prediction of DR, utilizing CNN and pretrained models, including DenseNet, Visual Geometry Group (VGG), ResNet, and Inception [19]. Moreover, specific study is required to enhance the efficiency of the deep learning framework [20]. Usman et al [4] observed that a pretrained CNN model detected lesions better, with 94.4% accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%